Stretchable conductive rubber based on blending process as well as preparation method and application of stretchable conductive rubber
By blending ethylene propylene ternary rubber and methylvinyl silicone rubber and undergoing two-stage vulcanization treatment, a stretchable conductive rubber material with high sensitivity and low resistance was prepared, which solved the problem of resistance response signal lag of tensile strain sensors under high frequency or large strain conditions, and improved the real-time and dynamic performance of the sensor.
Patent Information
- Application Number
- CN202411913799.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Tensile strain sensors have resistance response signal hysteresis problems under high frequency or large strain conditions, resulting in reduced real-time and accuracy, affecting the reliability of measurement data.
Using a preparation method based on the blending process, a stretchable conductive rubber material with high sensitivity and low electrical resistance is prepared by blending ethylene propylene ternary rubber with methylvinyl silicone rubber and undergoing two-stage vulcanization treatment.
It effectively reduces the hysteresis of resistive signals, improves the real-time and dynamic performance of the sensor, enhances flexibility and durability, improves resistance stability, and expands the application range.
Smart Images

Figure BDA0005206368200000061 
Figure BDA0005206368200000071 
Figure BDA0005206368200000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of rubber materials and strain sensing technology, and in particular to a stretchable conductive rubber based on a blending process and a preparation method and application thereof. Background Art
[0002] Stretchable strain sensors can sense the deformation of materials under external forces and convert them into electrical signals. They are widely used in health monitoring, flexible electronics, smart wearables, robots, and structural health monitoring. With the rapid development of flexible electronic technology, stretchable strain sensors have become a hot topic in research and application due to their excellent flexibility, stretchability and high sensitivity. The basic principle is to monitor strain by measuring the change in resistance of materials under external forces. They are usually used to detect deformation, displacement, pressure and other information of objects. In recent years, with the surge in demand for wearable devices, smart robots and biomedical devices, researchers are committed to developing stretchable strain sensors that can work stably and with high sensitivity under deformation conditions such as stretching and bending.
[0003] Although stretchable strain sensors have shown great application potential in many fields, they still face some technical challenges in actual use. In particular, the hysteresis of the output resistance response signal. When the sensor material is deformed, the resistance value will change accordingly. However, especially under higher frequencies or larger strain changes, the resistance response of the sensor does not immediately change synchronously with the external deformation. This delayed response phenomenon is usually called "signal hysteresis". The main reason for this phenomenon is the viscoelasticity of the material. Many materials used in stretchable strain sensors, such as conductive polymers, carbon nanotube composites, etc., have certain viscoelasticity. During strain loading and unloading, the material not only exhibits elastic strain, but also viscous strain. The strain hysteresis caused by the viscous component will cause the resistance response to lag, especially under high-frequency strain, this hysteresis effect will be more significant.
[0004] The problem of resistance response signal hysteresis seriously affects the real-time performance and accuracy of stretchable strain sensors, causing the stretchable strain sensors to be unable to accurately and timely reflect the rapid changes in the external environment, thereby affecting the reliability of the measurement data. In smart wearable devices or health monitoring, hysteresis may lead to incorrect physiological parameter analysis and affect the user's health management decisions. In robots or automated systems, delayed response may cause the control system to react slowly, affecting the efficiency and accuracy of task execution. In addition, delayed signals may also interfere with real-time data processing and feedback, increase system errors, and reduce the overall performance and application value of stretchable strain sensors. Therefore, solving the problem of resistance response signal hysteresis is the key to improving the performance of stretchable strain sensors. Summary of the invention
[0005] The purpose of the present invention is to provide a stretchable conductive rubber based on a blending process and a preparation method and application thereof in order to solve the above problems. The present invention prepares a stretchable conductive rubber with high sensitivity, excellent mechanical properties and low resistance hysteresis by an efficient, pollution-free and low-cost method, which can be used to prepare strain sensors.
[0006] In order to achieve its purpose, the present invention adopts the following technical solution:
[0007] A first aspect of the present invention provides a method for preparing a stretchable conductive rubber material based on a blending process, comprising the following steps:
[0008] S1. Preparation of EPDM rubber composite material and silicone rubber composite material:
[0009] Preparation of EPDM rubber composite material: by weight, 30-70 parts (preferably 50-70 parts) of EPDM rubber raw material, 2-6 parts of conductive filler, 3-7 parts of zinc oxide, 0.5-2.5 parts of stearic acid, 1.5-3.5 parts of accelerator, 1-3 parts of antioxidant, and 0.5-2.5 parts of sulfur are mixed and kneaded to obtain EPDM rubber composite material;
[0010] Prepare a silicone rubber composite material: by weight, take 30-70 parts (preferably 30-50 parts) of raw material methyl vinyl silicone rubber, 2-6 parts of conductive filler, 27-33 parts of silicon dioxide, 15-21 parts of hydroxy silicone oil, and 0.5-1.5 parts of vulcanizing agent, mix and knead to obtain a silicone rubber composite material;
[0011] S2. Blending:
[0012] The prepared EPDM rubber composite material and silicone rubber composite material are added with a compatibilizer, and the mass ratio of the starting raw materials of the composite material prepared in step S1, the EPDM rubber, the methyl vinyl silicone rubber and the compatibilizer is 30-70:30-70:3-7 (preferably 50-70:30-50:3-7) and mixed to obtain a mixture;
[0013] S3, vulcanization:
[0014] The mixed material prepared in step S2 is vulcanized in two stages, wherein the vulcanization temperature in the second stage is 20 to 30° C. higher than that in the first stage, to obtain a stretchable conductive rubber material.
[0015] Preferably, the raw material ratio of the EPDM rubber composite material is: 50-70 parts of EPDM rubber, 3-4 parts of conductive filler, 4-6 parts of zinc oxide, 1.0-2.0 parts of stearic acid, 2.0-3.0 parts of accelerator, 1-3 parts of antioxidant, and 1.0-2.0 parts of sulfur;
[0016] The raw material ratio of the silicone rubber composite material is: 30-50 parts of methyl vinyl silicone rubber, 3-4 parts of conductive filler, 29-31 parts of silicon dioxide, 17-19 parts of hydroxy silicone oil, and 0.8-1.2 parts of vulcanizing agent.
[0017] The mixing temperature of the mixing in step S1 is 30-50° C., the roller distance is 0.05-1 mm, the speed is 20-30 rpm, and the mixing process is 40-60 min;
[0018] The mixing temperature of the mixing in step S2 is 40-60° C., the roller distance is 0.05-1 mm, the speed is 40-60 rpm, and the mixing process is 60-80 min.
[0019] Preferably, in step S3,
[0020] The first stage of vulcanization has a vulcanization temperature of 150-170°C, a time of 10-20 min, and a pressure of 10-20 MPa. The preferred vulcanization temperature is 160-170°C, a time of 10-15 min, and a pressure of 10-15 MPa.
[0021] Then the second stage vulcanization treatment is carried out, the vulcanization temperature is 180-200°C, and the time is 2-4 hours.
[0022] Preferably, in step S3, the first stage vulcanization is carried out on a flat plate vulcanizer, and the second stage vulcanization is carried out in an oven.
[0023] In the process of the present invention, the vulcanization of the mixture is carried out in two stages. The first stage of vulcanization is mainly to vulcanize the conductive mixture into a shape and form a cross-linked network inside. The second stage of vulcanization is mainly to increase the cross-linking density of the first stage of vulcanization, so that the mechanical properties and aging resistance of the composite material can be improved.
[0024] The accelerator is selected from one or more of tetramethylthiuram disulfide, N-tert-butyl-2-benzothiazole sulfenamide, and dipentamethylenethiuram tetrasulfide;
[0025] The antioxidant is selected from one or more of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, 2-hydroxy-4-methoxybenzophenone, and 2,2,4-trimethyl-1,2-dihydroquinoline polymer.
[0026] The conductive filler is selected from multi-walled carbon nanotubes or conductive carbon black;
[0027] The vulcanizing agent is selected from one or more of dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl perbenzoate, and dibenzoyl peroxide;
[0028] The compatibilizer is selected from one or more of γ-aminopropyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, and maleic anhydride grafted compatibilizer.
[0029] The conductive filler has a length of 10-20 μm, a diameter of 7-9 nm, and a specific surface area of 100-200 m 2 / g;
[0030] The density of the EPDM rubber is 0.85-0.9 g / cm 3 , molecular weight is 15×10 4 g / mol;
[0031] The vinyl content of the methyl vinyl silicone rubber is 0.16% and the molecular weight is 7.2×10 5 g / mol;
[0032] The silica particle size is 7-40nm and the specific surface area is 200m 2 / g;
[0033] The hydroxyl content of the hydroxy silicone oil is 7-9% and the viscosity is 25-30 Pa·s.
[0034] A second aspect of the present invention provides a stretchable conductive rubber material, which is prepared by any of the preparation methods described above.
[0035] A third aspect of the present invention provides use of the above-mentioned stretchable conductive rubber material in preparing a flexible strain sensor.
[0036] The beneficial effects of the present invention are:
[0037] 1. Improve response speed: After EPDM rubber is blended with methyl vinyl silicone rubber, the elasticity of the material can be effectively improved, so that the sensor can respond to external deformation changes more quickly, reduce the hysteresis of the resistance signal, and improve the real-time and dynamic performance of the stretchable strain sensor.
[0038] 2. Enhanced flexibility and durability: The conductive rubber material prepared by blending has excellent stretchability and wear resistance, can maintain stable performance in a working environment of repeated stretching and bending, and reduce the resistance signal lag caused by material fatigue, thereby improving the long-term reliability of the stretchable strain sensor.
[0039] 3. Improve resistance stability: The blend of EPDM rubber and methyl vinyl silicone rubber can optimize the volume conductivity change characteristics of the material, so that when the conductive rubber material of the present invention is used as a stretchable strain sensor, the resistance signal is more stable during the strain change process, reducing the influence of external environmental temperature, humidity and other factors, and improving measurement accuracy.
[0040] 4. Expand the scope of application: Since the blended conductive rubber material has excellent weather resistance, oxidation resistance and chemical stability, it can be widely used in various harsh environments. It can also be used in wearable devices, smart medical care, robot control and other fields, expanding the application scenarios of stretchable strain sensors.
[0041] The light-weight, highly elastic stretchable conductive rubber material prepared by the method of the present invention has the advantages of good volume conductivity, excellent mechanical properties, high sensitivity, low resistance hysteresis, etc. It can be applied as a strain sensor, suitable for damage monitoring under human physiology and large components; and promote the development of the field of intelligent sensing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The present invention is a flow chart of the method for preparing the conductive rubber material.
[0043] Figure 2 This is a physical picture of the conductive rubber material prepared in Example 4.
[0044] Figure 3 The SEM microscopic morphology images of the flexible strain sensors of Comparative Example 2 and Example 4 are shown.
[0045] Figure 4 It is a comparison chart of the output monitoring signals of the conductive rubber materials prepared in Example 4 and Comparative Example 2. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.
[0047] The experimental methods in the following examples are conventional methods unless otherwise specified.
[0048] The raw materials are: ethylene propylene diene monomer rubber (EPDM) and methyl vinyl silicone rubber (VMQ) as the matrix, multi-walled carbon nanotubes (MWCNT) as the conductive filler, zinc oxide, stearic acid, accelerator tetramethylthiuram disulfide (accelerator TMTD, CAS No. 137-26-8), antioxidant N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (antioxidant 6PPD, CAS No. 793-24-8), and sulfur (S) as fillers for EPDM. Nano-silica, hydroxy silicone oil (PDMS), and diisopropyl peroxide (curing agent DCP) are used as fillers for methyl vinyl silicone rubber. γ-Aminopropyl triethoxysilane (silane coupling agent KH-550, CAS No. 919-30-2) is used as a compatibilizer for EPDM and methyl vinyl silicone rubber.
[0049] Among them, the multi-walled carbon nanotubes are 10-20 μm long, 7-9 nm in diameter, and have a specific surface area of 100-200 m 2 / g;
[0050] The density of EPDM rubber is 0.85-0.9g / cm 3 , molecular weight is 15×10 4 g / mol;
[0051] Zinc oxide, stearic acid, antioxidant, accelerator, and sulfur were all analytically pure;
[0052] The vinyl content of methyl vinyl silicone rubber is 0.16% and the molecular weight is 7.2×10 5 g / mol;
[0053] Silica particle size 7-40nm, specific surface area 200m 2 / g;
[0054] The hydroxyl content of hydroxy silicone oil is 7-9% and the viscosity is 25-30 Pa·s;
[0055] Dicumyl peroxide was of analytical grade, and γ-aminopropyltriethoxysilane was of reagent grade.
[0056] All of the above raw materials are commercially available conventional commodities.
[0057] The preparation method of the stretchable conductive rubber material of the present invention is as follows (process flow chart as shown in Figure 1 shown):
[0058] S1. Preparation of EPDM rubber composite material and silicone rubber composite material:
[0059] The EPDM rubber, multi-walled carbon nanotubes, zinc oxide, stearic acid, accelerator, antioxidant, and sulfur were sequentially put into a double-roll mill and mixed evenly at a mixing temperature of 50°C, a roller distance of 1mm, a speed of 30rpm, and a mixing process of 40min to prepare an EPDM rubber composite material.
[0060] Methyl vinyl silicone rubber, multi-walled carbon nanotubes, silicon dioxide, hydroxy silicone oil, and dicumyl peroxide were placed in a double-roll mill and mixed evenly at a mixing temperature of 50°C, a roller distance of 1 mm, a speed of 30 rpm, and a mixing process of 40 minutes to prepare a silicone rubber composite material.
[0061] S2. Blending:
[0062] The prepared EPDM rubber composite material and silicone rubber composite material were mixed on a double-roll mill and 5 parts of silane coupling agent KH-550 were added. The mixing temperature was 60° C., the roller distance was 1 mm, the speed was 40 rpm, and the mixing process was 60 minutes to obtain a mixed material.
[0063] In this process, two rollers rotate relative to each other at different speeds in a twin-roll mill. The internal and external friction and the shear force between the rollers cause the material to deform and flow. The matrix and filler are dispersed, disconnected and recombined under the action of this shear force. The shearing action allows the filler to be effectively dispersed in the matrix. A three-dimensional tunneling conductive network structure is formed inside it, which has the ability to collect response signals.
[0064] S3, vulcanization:
[0065] The mixture prepared in step S2 was vulcanized in the first stage on a flat vulcanizer at a vulcanization temperature of 170°C, a time of 15 min, and 15 MPa. It was then placed in a blast drying oven (or vacuum oven) for a second stage vulcanization treatment at a vulcanization temperature of 200°C and a time of 2 h to obtain a stretchable conductive rubber material. Figure 2 This is a physical picture of the conductive rubber material prepared in Example 4.
[0066] The first stage of the vulcanization process causes the cross-linking reaction between EPDM rubber and methyl vinyl silicone rubber to begin. The peroxide (diisopropylbenzene peroxide) decomposes to produce free radicals, which react with the double bonds in the rubber molecules to form a cross-linked structure. The cross-linking formation at this stage is mainly initiated by the vulcanizing agent. The sulfur reacts with the unsaturated groups in the rubber to form cross-linking points, which transforms the rubber from a linear structure to a three-dimensional network structure. The vulcanization reaction promotes the initial cross-linking of the rubber material. Although the degree of cross-linking is not complete, the elasticity and plasticity of the material have been improved to a certain extent, and the mechanical properties and heat resistance of the material have been initially enhanced.
[0067] The second stage of vulcanization is in a blast drying oven. High temperature treatment can further enhance the crosslinking degree and promote the continued reaction between sulfur and double bonds in rubber molecules. The increase in crosslinking density makes the molecular structure of the material more stable, thereby improving its thermal stability, physical properties and aging resistance. Further completion of the crosslinking reaction makes the material structure more stable, and ultimately obtains ideal mechanical properties and durability.
[0068] The conductive rubber material products of Examples 1-4 in Table 1 were prepared according to the above method. The raw material ratios used in each example are shown in Table 1 (the values in Table 1 are weight percentages of the components).
[0069] Table 1
[0070]
[0071] The methyl vinyl silicone rubber composite material or EPDM rubber composite material prepared in Examples 1 and 2 is not subjected to step S2, but directly subjected to the two-stage vulcanization of step S3 to obtain the conductive rubber material.
[0072] At the same time, comparative example 1-2 was prepared:
[0073] Comparative Example 1 (using the same raw materials as the present invention, but different processes)
[0074] Using the raw materials and dosage of Example 4, all raw materials, namely methyl vinyl silicone rubber, EPDM rubber, multi-walled carbon nanotubes, zinc oxide, stearic acid, accelerator, antioxidant, sulfur, silicon dioxide, dicumyl peroxide, are directly and simultaneously put into an open mill for mixing, and the temperature is set to 50°C, the speed is 70rpm, the roller distance is 1mm, and the time is 50min. Then put it into a flat vulcanizer at a pressure of 10MPa, a temperature of 170°C, and a time of 10min, and perform the first stage vulcanization molding to obtain.
[0075] Comparative Example 2 (using different raw materials and the same process as the present invention)
[0076] The raw materials used in comparative example 2 are different from those of the present invention. Specifically, the filler in comparative example 2 includes EPDM rubber, methyl vinyl silicone rubber, conductive carbon black, silicon dioxide, cyclohexane oil, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (curing agent bis-25). The conductive rubber material is prepared by the preparation process of the present invention.
[0077] Specifically, the preparation process is as follows: 70 parts of EPDM rubber, 20 parts of conductive carbon black, and 2 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane are put into a double-roll mill and mixed evenly, the mixing temperature is 50°C, the roller distance is 1mm, the speed is 30rpm, and the mixing process is 40min. Prepare EPDM rubber composite material. 30 parts of methyl vinyl rubber, 20 parts of conductive carbon black, 40 parts of silica, 24 parts of cyclohexane oil, and 2 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane are put into a double-roll mill and mixed evenly, the mixing temperature is 50°C, the roller distance is 1mm, the speed is 30rpm, and the mixing process is 40min. Prepare methyl vinyl silicone rubber composite material. Mix EPDM rubber composite material and silicone rubber composite material on a double-roll mill. The mixing temperature is 60°C, the roller distance is 1mm, the speed is 40rpm, and the mixing process is 60min. Then, the first stage of vulcanization was carried out on a flat vulcanizer at a vulcanization temperature of 170°C, a time of 15 minutes, and a pressure of 15 MPa. The second stage of vulcanization was carried out in a blast drying oven at a temperature of 200°C and a time of 2 hours. A stretchable conductive rubber material was obtained.
[0078] Performance Testing
[0079] The properties of the prepared flexible conductive rubber material were tested.
[0080] (1) Volume conductivity: The volume conductivity of the conductive nano rubber material is tested according to the GT / T1692-2008 standard. First, the sample is cut into a standard sample of 40mm×10mm×1mm (the surface is cleaned with anhydrous ethanol), and the resistance value of the sample in the unstrained state is measured using a Keysight 34465A digital multimeter. The average resistance value within 1s of the digital multimeter is collected, and the average value is taken for each group of 3 test strips. The volume conductivity formula is defined as:
[0081]
[0082] In formula (1), σ is the volume conductivity (S / m), ρ is the volume resistivity of the material (Ω·m), R is the volume resistance (Ω), L is the length of the sample (m), and S is the cross-sectional area (m 2 ).
[0083] (2) Sensitivity test: Clamp the two ends of the conductive nano rubber material on an electronic universal testing machine, take a wire, connect one end of the wire to the conductive nano rubber material, and the other end of the wire to a digital multimeter. Set the strain through the universal testing machine. After a single stretching cycle, the maximum resistance value is transmitted to the computer through the digital multimeter, and then the sensitivity is calculated through the resistance and strain according to formula (2).
[0084] Sensitivity calculation method: Equation (2) is used to evaluate the sensitivity of the composite material:
[0085] GF=(ΔR / R0) / ε Formula (2)
[0086] In formula (2), ε is strain. ΔR / R0, ΔR=R-R0, where R0 is the initial resistance and R is the test resistance.
[0087] (3) Test method for resistance hysteresis: Cut the conductive nano rubber material into strips of 40 mm × 40 mm × 1 mm, fix the sample on an electronic universal testing machine for a cyclic loading-unloading test, and use a digital multimeter to record the resistance hysteresis change (see the results). Figure 4 ).
[0088] (4) Mechanical properties test method: According to GB / T528-2009, the mechanical properties of dumbbell-shaped standard conductive nano-rubber material specimens were measured using an electronic universal testing machine (DDL10) at a tensile rate of 200 mm / min. -1 , and take the average value of 3 groups of experimental data.
[0089] The performance test results are shown in Table 2.
[0090] Table 2: Conductive rubber material performance results
[0091]
[0092] It can be seen from the various embodiments and comparative examples that the volume conductivity of the embodiments of the present invention is significantly reduced compared with comparative example 1 or comparative example 2. In particular, compared with comparative example 1, the volume conductivity of embodiment 4 using the same filler is reduced more significantly, indicating that the blending process of the present invention can greatly reduce the volume conductivity.
[0093] All the examples can achieve good sensitivity. Compared with Comparative Example 1 or Comparative Example 2 which use raw materials or preparation methods different from those of the present invention, the sensitivity of each example is improved to varying degrees.
[0094] After the two rubbers are mixed, the cross-linking structure can be optimized through appropriate processing and vulcanization conditions to form a more uniform and stronger three-dimensional cross-linked network. This structure helps to enhance the mechanical properties of the overall material, especially in terms of tensile strength and elongation at break. Compared with Comparative Example 1 or Comparative Example 2, the tensile strength and elongation at break of each embodiment are improved. In particular, the tensile strength and elongation at break of Example 4 using the filler ratio and blending process of the present invention are most significantly improved.
[0095] Through the SEM microscopic morphology of comparative example 2 and example 4 ( Figure 3 ) It can be seen that the conductive carbon black of Comparative Example 2 has serious agglomeration in the rubber matrix, which hinders the continuity of the conductive filler in the rubber matrix. The self-assembled conductive filler of Example 4 has good dispersion in the rubber matrix, which is also an important factor in obtaining low volume conductivity, high sensitivity, good mechanical properties, and stable resistance / strain response signals.
[0096] The resistance / strain response signal diagram of comparative example 2 and example 4 ( Figure 4 ) It can be seen that the resistance of the signal graph of comparative example 2 tends to be stable as the number of cycles increases. The resistance / strain response signal graph of Example 4 remains stable, and there is no trend of the resistance / strain response signal rising first and then falling. The resistance / strain response signal is always stable; this is because EPDM rubber usually has good elastic properties and can recover quickly when stressed; while methyl vinyl silicone rubber has low internal friction, which prevents excessive energy loss during repeated deformation; the composite material formed by the blending of the two can produce a synergistic effect during deformation, slowing down the resistance hysteresis effect of the material.
[0097] Through the method of the present invention, with a specific mass ratio of EPDM rubber to methyl vinyl silicone rubber and a specific vulcanization system combined with multi-walled carbon nanotubes, a stretchable strain sensor with low volume conductivity, high sensitivity, good mechanical properties, and low resistance hysteresis can be produced, and the innovative ratio of the raw materials of the present invention enables the stretchable conductive rubber material to reduce the resistance hysteresis in the monitoring signal, so that it has a stable monitoring signal; the conductive nano rubber material of the present invention can be made into a flexible strain sensor, which is applied to real-time strain monitoring of seismic isolation bearings, human physiological monitoring, etc. At the same time, the stretchable conductive rubber material can overcome the defects of traditional strain sensors such as brittleness, low sensitivity, and narrow monitoring range. The monitoring signal output during the monitoring process is perfectly coordinated with the deformation of the measured structure, which is more conducive to real-time monitoring of the object. The present invention can promote the development of intelligent sensing technology.
Claims
1. A method for preparing a stretchable conductive rubber material based on a blending process, characterized in that: The steps include: S1. Preparation of EPDM rubber composite material and silicone rubber composite material: Preparation of EPDM rubber composite material: by weight, 30-70 parts of EPDM rubber raw material, 2-6 parts of conductive filler, 3-7 parts of zinc oxide, 0.5-2.5 parts of stearic acid, 1.5-3.5 parts of accelerator, 1-3 parts of antioxidant, and 0.5-2.5 parts of sulfur are mixed and kneaded to obtain EPDM rubber composite material; Prepare a silicone rubber composite material: by weight, take 30-70 parts of raw material methyl vinyl silicone rubber, 2-6 parts of conductive filler, 27-33 parts of silicon dioxide, 15-21 parts of hydroxy silicone oil, and 0.5-1.5 parts of vulcanizing agent, mix and knead to obtain a silicone rubber composite material; S2. Blending: The prepared EPDM rubber composite material and silicone rubber composite material are added with a compatibilizer, and the starting raw materials of the composite material prepared in step S1, EPDM rubber, methyl vinyl silicone rubber and the compatibilizer are mixed in a mass ratio of 30-70:30-70:3-7, and kneaded to obtain a mixture; S3, vulcanization: The mixed material prepared in step S2 is vulcanized in two stages, wherein the vulcanization temperature in the second stage is 20 to 30° C. higher than that in the first stage, to obtain a stretchable conductive rubber material.
2. The preparation method according to claim 1, characterized in that: The raw material ratio of the EPDM rubber composite material is: 50-70 parts of EPDM rubber, 3-4 parts of conductive filler, 4-6 parts of zinc oxide, 1.0-2.0 parts of stearic acid, 2.0-3.0 parts of accelerator, 1-3 parts of antioxidant, and 1.0-2.0 parts of sulfur. The raw material ratio of the silicone rubber composite material is: 30-50 parts of methyl vinyl silicone rubber, 3-4 parts of conductive filler, 29-31 parts of silicon dioxide, 17-19 parts of hydroxy silicone oil, and 0.8-1.2 parts of vulcanizing agent.
3. The preparation method according to claim 1, characterized in that: The mixing temperature of the mixing in step S1 is 30-50° C., the roller distance is 0.05-1 mm, the speed is 20-30 rpm, and the mixing process is 40-60 min; The mixing temperature of the mixing in step S2 is 40-60° C., the roller distance is 0.05-1 mm, the speed is 40-60 rpm, and the mixing process is 60-80 min.
4. The preparation method according to claim 1, characterized in that: In step S3, The first stage of vulcanization has a vulcanization temperature of 150-170°C, a time of 10-20 min, and a pressure of 10-20 MPa. The preferred vulcanization temperature is 160-170°C, a time of 10-15 min, and a pressure of 10-15 MPa. Then the second stage vulcanization treatment is carried out, the vulcanization temperature is 180-200°C, and the time is 2-4 hours.
5. The preparation method according to claim 4, characterized in that: In step S3, the first stage vulcanization is carried out on a flat plate vulcanizer, and the second stage vulcanization is carried out in an oven.
6. The preparation method according to claim 1, characterized in that: The accelerator is selected from one or more of tetramethylthiuram disulfide, N-tert-butyl-2-benzothiazole sulfenamide, and dipentamethylenethiuram tetrasulfide; The antioxidant is selected from one or more of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, 2-hydroxy-4-methoxybenzophenone, and 2,2,4-trimethyl-1,2-dihydroquinoline polymer.
7. The preparation method according to claim 1, characterized in that: The conductive filler is selected from multi-walled carbon nanotubes or conductive carbon black; The vulcanizing agent is selected from one or more of dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl perbenzoate, and dibenzoyl peroxide; The compatibilizer is selected from one or more of γ-aminopropyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, and maleic anhydride grafted compatibilizer.
8. The preparation method according to claim 7, characterized in that: The conductive filler has a length of 10-20 μm, a diameter of 7-9 nm, and a specific surface area of 100-200 m 2 / g; The density of the EPDM rubber is 0.85-0.9 g / cm 3 , molecular weight is 15×10 4 g / mol; The vinyl content of the methyl vinyl silicone rubber is 0.16% and the molecular weight is 7.2×10 5 g / mol; The silica particle size is 7-40nm and the specific surface area is 200m 2 / g; The hydroxyl content of the hydroxy silicone oil is 7-9% and the viscosity is 25-30 Pa·s.
9. A stretchable conductive rubber material, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. Use of the stretchable conductive rubber material according to claim 9 in preparing a flexible strain sensor.
Citation Information
Patent Citations
Silicone rubber and EPDM (Ethylene-Propylene-Diene Monomer) blended rubber composite vulcanization system and preparation method thereof
CN110358201A